Selfcare deficits in elderly 75 and more years old patient's after discharge from hospital, gone into medical surgical units from University Hospital La Paz - Mª Luisa Martínez Martín; Mª del Coro Canalejas Pérez; Manuel Luis Vera Cortés; Mª Luisa Cid Galán; Carmen Martín Salinas; Ángel Otero Puime (Fundación para el Desarrollo de la Enfermería, 2010)
General objective: Consider the selfcare deficit in elderly 75 and more years old after discharge from hospital's medicalsurgical unit.Secondary objectives: Identify factors related with selfcare deficit in 75 and more years old patient's at the moment hospital discharge; Establish nursing diagnosis that determine selfcare deficits in 75 and more years old patient's at the moment hospital discharge; Mark selfcare requirements affected higher in 75 and more years old patient's at the moment hospital discharge; Determine selfcare deficit evolution's in 75 and more years old patient's at the moment hospital discharge. Design: Observational, analytic and longitudinal study. Subjects of study: 400 elderly patients 75 and more years old after medicalsurgical units discharge from de University Hospital La Paz.Variables: Basic conditional factors of selfcare agency. Factors to affect selfcare requirements regulation. Diagnosis nursing that determine selfcare deficit.Instrument: Nursing appraisal document, Barthel's scale and Pfeiffer questionnaireField work: First interview at the moment hospital discharge, second interview two months after hospital discharge. Data analysis: Descriptive analysis sample's variables and possible differences in selfcare deficit in two phases of study anyway possible relations with other factors.